Design of a reconfigurable wheelchair with stand-sit-sleep capabilities for enhanced independence of long-term wheelchair users - Desai, Sumit; Mantha, Shankar; Phalle, Vikas (Technology and disability, 2018)
The wheelchair users are exposed to many physical and psychological health problems associated with prolonged seated posture with being inactive in wheelchair, e.g., fatigue, pain in hip joint, pressure sores, etc. Other related issues are increase in caregiver dependency, lower back pains among caregivers, and injury incidences during transfer support, etc. Many elderly subjects who can walk are confined in wheelchairs due to the lack of standing ability. With fewer caregivers and increased numbers of lower limb disabled and elderly subjects, there is a significant need of improved wheelchair designs aimed at enhanced independence of wheelchair users. The focus of present work was at designing a novel reconfigurable wheelchair incorporated with stand-sit-sleep capabilities for the purpose of enhancement of independence and quality of life of lower limb disabled and elderly subjects. In the early part of the study, the integration of QFD (Quality function deployment) and TRIZ (Theory of Inventive problem solving) approaches was employed to structure and explore long term wheelchair user needs to identify critical design parameters and to solve possible design contradictions. Further work presents an overall product design and development phases of a reconfigurable wheelchair. The major contributions of paper can be summarized as (i) Kinematic concept of a reconfigurable wheelchair with single DoF based on QFD design and TRIZ methodology (ii) Graphical synthesis of new wheelchair mechanism (iii) Modelling of a proposed wheelchair using Top down modelling approach (iv) Analysis of model using multi-body dynamics (MBD) simulations using MSC ADAMS and shape optimization using ANSYS and (v) Product realization through 3D printed functional model. The proposed inventive solution to the problems of long-term wheelchair users has a promising potential to enhance independence and quality of life of disabled people.